2011
DOI: 10.1021/jp208936r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supported Gold on the Dynamics of Reduction and Crystallization of Iron Oxides: A Dispersive X-ray Absorption Near Edge Structure Spectroscopy and X-ray Diffraction Study

Abstract: Iron oxide-supported gold samples were characterized by X-ray absorption near edge structure (XANES) spectroscopy during treatments in flowing H 2 at increasing temperature. Spectra were recorded at the Au L III and Fe K edges to monitor the reduction of both metals and to determine the influence of gold on the reducibility of the support. The results show that reduction of Fe 3+ to Fe 2+ on the support occurs at lower temperatures in samples containing gold than on samples of the bare support, with the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…The reduction of Fe 2 O 3 to Fe 3 O 4 in the pure oxide-support occurred at 345 °C, while it shifted to around 200 °C in the Au/Fe 2 O 3 catalyst, suggesting that the Au particles facilitated the reduction of Fe 2 O 3 via the hydrogen spillover effect. H 2 was adsorbed and activated on the Au particles, and the dissociated hydrogen atoms diffused from the Au particle to the surface of Fe 2 O 3 , accelerating the reduction of Fe 2 O 3 . , …”
Section: Resultsmentioning
confidence: 99%
“…The reduction of Fe 2 O 3 to Fe 3 O 4 in the pure oxide-support occurred at 345 °C, while it shifted to around 200 °C in the Au/Fe 2 O 3 catalyst, suggesting that the Au particles facilitated the reduction of Fe 2 O 3 via the hydrogen spillover effect. H 2 was adsorbed and activated on the Au particles, and the dissociated hydrogen atoms diffused from the Au particle to the surface of Fe 2 O 3 , accelerating the reduction of Fe 2 O 3 . , …”
Section: Resultsmentioning
confidence: 99%
“…Zacl et al have reported that the problem of deactivation is likely to be universal for all noble metal/ceria system in which a significant fraction of hydrogen in the feed creates a reducing environment facilitates the over-reduction of the support. Recently, Jimenez-Lam et al used an in situ dispersive XANES probe to determine that in the case of Au/Fe 2 O 3 the reduced gold provides sites for H 2 adsorption and dissociation, which is then spillover from the gold to the support, favoring its reduction and restructuring. Our results for Au/CeO 2 seem to agree with those of Jimenez-Lam et al .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the amount of surface oxygen species, which might be removable during the redox cycles, varied with the size of Au NPs: 27 % on Au‐573, 20 % on Au‐673 and 17 % on Au‐723 (Table S2). These surface oxygen species might be located at the Au‐Fe 2 O 3 interfacial perimeters and actively participated in the strong metal–support interactions …”
Section: Figurementioning
confidence: 99%